Effect of cobalt chloride on protein profiling in chlorella vulgaris - DR. G. P. SINGH,; RAVINDRA KUMAR SAINI,; AMRIT DAIYA, (International Journal of Pharma and Bio Sciences, 2017)
Cobalt is an essential redox active transitional metal that is necessary at very low concentration for normal growth & reproduction of algae. Chlorella vulgaris beijerinck is a single cell green algae belonging to class Chlorophyceae. Cultures of Chlorella vulgaris were treated with 0.5ppm, 2ppm, 4ppm and 6ppm cobalt chloride separately and observed the effect on total protein content, but expression of some specific proteins were increased in cobalt treated cultures. It was observed that in comparision to the corresponding control there were four polypeptide bands which were found to be overly expressed: S1, at concentrations of 4 ppm and S2, S3 and S4 at were at 2 ppm.